Cytogenetic investigations in Bornean Rhinolophoidea revealed cryptic diversity in Rhinolophus sedulus entailing classification of Peninsular Malaysia specimens as a new species - MARIANNE, VOLLETH; Faisal Ali, Anwarali Khan; STEFAN, MÜLLER; Robert J., Baker; DANIELA, ARENAS-VIVEROS; RICHARD D., STEVENS; Vladimir, TRIFONOV; THOMAS, LIEHR; HELLER, KLAUS-GERHARD; Cibele G., Sotero-Caio (BioOne, 2021)
Classical and molecular cytogenetic methods were applied to study the karyotypes of one species of Hipposideridae and three taxa of the Rhinolophidae subgenus Aquias from Malaysian Borneo. Except for four chromosomal pairs with autapomorphic arm combinations, the karyotype of Coelops robinsoni was found to be similar to the closely related Aselliscus stoliczkanus. From the three Rhinolophus taxa studied, only R. trifoliatus was found to share the karyotype with conspecifics from Peninsular Malaysia. In contrast, the karyotype of R. luctus foetidus from Sarawak, Borneo differed in the composition of the Y-autosomal translocation products from the closely related R. morio from Peninsular Malaysia, formerly also a subspecies of R. luctus. Therefore, elevation to specific rank is suggested for R. l. foetidus. Examination of the chromosomal set of male R. sedulus specimens from Borneo with 2n = 45 and a Neo-X1X2Y sex chromosome system revealed extreme differences to the karyotype of specimens from Peninsular Malaysia with 2n = 28, to date also classified as R. sedulus. Therefore, with Sarawak, Borneo, as the type locality for R. sedulus, the taxon from Peninsular Malaysia is here described as a new species.